Kapasitas Politik dan Kualitas Demokrasi di Era Covid 19 pada PILKADA Kota Medan tahun 2020 - Eddy Iriawan; Bengkel Ginting; Warjio Warjio (Universitas Medan Area, 2023)
The purpose of writing this article is to analyze the political capacity, policies of the Medan city government and the quality of democracy in the implementation of the 2020 Medan City Pilkada during the Covid 19 period. The type of research used is qualitative research because by using this type of research researchers can easily interview informants in the field by examining the problem phenomenologically which makes it easier for researchers to obtain data through experience, and informants both orally and in writing. Thus, helping researchers to obtain concrete data related to the level of Community Participation with special needs which is reviewed based on the community's response to the Implementation of the 2020 Legislative Election. In terms of political capacity, the regional elections are still being held because they are based on three main aspects, namely the first is the philosophical aspect which emphasizes that Pilkada is a form of embodiment of people's sovereignty. Second: the health protection system for participants, organizers and voters in the process of holding the 2020 regional elections amid a pandemic is in the sub-optimal category. Third: The ideal election or pilkada in the Covid-19 pandemic situation is to reconceptualize the election administration system from a substance aspect which includes the stages of updating voter data, verifying individual candidates, and campaigning using the online method and using the E-Votting method in voting. As well as the existence of public and voter compliance to the level of internalization.